The neuroscientific substrate of psychotherapy: mechanisms and brain areas affected by psychotherapeutic processes - Seliniotaki, Theodora; Nestoras, Ioannis N. (Psychology: the Journal of the Hellenic Psychological Society, 2017)
Recently we witness a general tendency to synthesize psychotherapeutic models, as well as, a tendency to explore the effects of psychotherapy on the brain. This article summarizes a large volume of literature on the neuroscientific substrate of psychotherapy starting with scientific findings located in Ancient times till recent literature. The published literature that deals with the effects of psychotherapy on the brain includes studies, usually neuroimaging ones, which examine the neurological aspects of the most popular models of psychotherapy and pharmacotherapy. All researchers draw the conclusion that psychotherapy affects the brain functions, such as neuroplasticity, learning and memory, neurogenesis, mood and emotions, thus leading to an improvement of mental health. The discussion leads to the constitution of a new discipline, the Neuropsychotherapy, which is promising for the liberation from the grip of psychiatric disorders.